Experimental investigation and performance analysis of a direct-driven linear generator. (December 2017) - Zou, Huiming; Wang, Min; Tang, Mingsheng; Li, Can; Tian, Changqing
Abstract: Electricity generation of renewable sources has got great development to reduce the usage of fossil fuels. Linear generator is a newly-developing orientation to utilize the power with reciprocating movement. In the paper, the structure and principle of the direct-driven linear generator (DLG) are introduced. The induction electromotive force is given in detailed based field & circuit method. Meanwhile, the paper introduces the design, fabrication and testing of a DLG prototype, theoretical model of the free-piston engine is presented, and the DLG operation driven by Simulated Power Source (SPS) is discussed. Furthermore, the performance of the system is investigated in detail under different conditions. The results show that, there is an optimal capacitance to get the highest coefficient, which is 25μF here. The frequency has obvious effect on the output at lower load resistance, but it has little effect on the efficiency, the efficiency depends more on the ratio of the load resistance and generator internal resistance. Lastly, according to the analysis results with the phasor algorithm analysis, the proposed model and analytical method are correct and effective. The DLG has a good application prospect in the energy conversion field.